Mempertimbangkan Hermeneutika sebagai Metode Tafsir Al-Qurâan - Maulana, Asep Shodiq (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2009)
Daâwah as process of actualizing Islamic message in theÂ real life context in turn will weigh of grasp position to Al Quran text. Islamic massage is sent awayÂ dialoguableÂ with various socials environmental condition. In this condition it is needed one of relevant methodology in understanding Al-Qurâan.Â The methodology is a method can catch meaning of text that cant only by rely grasp of language grammar corner only, but also socials context grasp of that text. That method is named hermeneutika.